Outcome measurement for gender-affirming care in Canada: a systematic review - Cynthia Chan; Rakhshan Kamran; Liam Jackman; Micon Garvilles (BMJ Open)
Introduction Gender-affirming care (GAC) includes interventions aimed at supporting an individual’s gender identity. Canada is experiencing an increase in referrals for GAC, higher than any other health service; therefore, there is a need for a systematic approach to health outcome measurement to effectively evaluate care. This review aims to analyse health outcome measurement in Canadian GAC, focusing on what is measured, how it is measured and associated barriers and enablers.Methods A comprehensive search was conducted in MEDLINE, Embase, PsycINFO, Scopus and CINAHL, up to 26 December 2023. Inclusion criteria were original articles involving transgender or gender-diverse (TGD) patients receiving gender-affirming care in Canada.Results A total of 4649 articles were identified with 64 included, representing 6561 TGD patients. Most studies were conducted in Ontario (52%), British Columbia (19%) and Quebec (11%). The most common forms of GAC provided were hormonal (36%) and surgical (27%). Barriers to outcome measurement include that most studies (61%) did not use patient-reported outcome measures (PROMs). When PROMs were used, most did not capture gender-related constructs (eg, gender dysphoria). Barriers to accessing care included stigma, discrimination, lack of clinician knowledge, geographic, socioeconomic and institutional barriers.Conclusion This review reveals gaps in outcome measurement for GAC, particularly underutilisation of PROMs and inconsistent outcome measurement and reporting. There is a need to systematically implement PROMs, including those measuring gender-related constructs, to promote patient-centred care. This review provides evidence-based recommendations for improving health outcomes for TGD individuals in Canada.